Evaluation of anxiolytic activity of aqueous extract of Coriandrum sativum Linn. in mice: A preliminary experimental study - Latha, K. (Pharmacognosy Res, 2015)
OBJECTIVES: To evaluate the anxiolytic effect of Coriandrum sativum (CS) aqueous extract in mice. To compare the antianxiety activity of CS against standard drug diazepam (3 mg/kg). MATERIALS AND METHODS: After obtaining Institutional Animal Ethics Committee approval, Swiss albino mice (18–25 g) of either sex were randomly divided into five groups of six animals each. Dried powder of CS leaves was boiled with distilled water, cooled, filtered, placed on a hotplate for complete evaporation, finally weighed and stored. The control group, test group, and standard drugs group received saline, CS extract (50, 100, and 200 mg/kg), diazepam (3 mg/kg), respectively, by oral feeding. The antianxiety effect was assessed by elevated plus maze (EPM) in mice. RESULTS: In EPM, it implied that CS 50 mg/kg (Group III), 100 mg/kg (Group IV), and 200 mg/kg (Group V) significantly (P < 0.001) increases the number of entries in open arms compared to control. The time spent in open arms also increased in all the doses of CS extract significantly. CONCLUSION: The current study demonstrates statistically significant dose-dependent antianxiety activity of CS leaves.